Murder your darlings : a novel - Blum, Jenna (Harper, 2026)
"For every woman who's ever fallen for a bad man comes a hilarious and eviscerating tale of love, loss, and deadlines from New York Times bestselling author Jenna Blum. Known for such brilliant historical novels as Those Who Save Us and The Lost Family, A Mighty Blaze co-founder and New York Times bestselling author Jenna Blum now offers a contemporary, suspenseful novel about love, loss, and revenge in the world of books. Simone "Sam" Vetiver is a mid-career novelist finishing a lukewarm publicity tour while facing a deadline for a new book on which she's totally blocked. Recently divorced, Sam is worrying where her life is going when she receives glowing fan mail from Stratospherically Successful author William Corwyn, renowned for his female-centric novels. When William and Sam meet and his literary sympathy is as intense as their chemistry, both writers think they've found The One. But as in their own novels, things between Sam and William are not what they seem. William has multiple stalkers, including a scarily persistent one named The Rabbit. He lives on a remote Maine island, where his writer life resembles The Shining. And when writers turn up dead, including from The Darlings support group William runs, Sam has to ask: Is it The Rabbit-William's #1 Stalker? Another woman scorned? Can William be everything he seems? Narrated by Sam, William, and The Rabbit, Murder Your Darlings is a wickedly witty look at today's literary landscape and down-the-rabbit-hole tale of how far people will go for love"-- Provided by publisher.